X-ray studies concerning the structure of 6-phosphogluconate dehydrogenase - Helliwell, J; Helliwell, John (1977)
This thesis is concerned with the structure determination of 6-phosphogluconate dehydrogenase (6-phospho-D-gluconate:NADP+ oxidoreductase (decarboxylating), E.C.1.1.1.44) from sheep liver. This protein is the second enzyme in the pentose phosphate pathway and catalyses the conversion of 6-phosphogluconate to ribulose-5-phosphate and CO2. Chapter 1 gives an introduction to the chemical properties of 6-phosphogluconate dehydrogenase (6PGDH) and compares these properties for the enzyme from a variety of sources. The common structural features of the NAD+-dependent dehydrogenases are discussed in terms of divergent and convergent evolution. Details of an NADP+-dependent enzyme, E.coli dihydrofolate reductase are also given. This is the only published high resolution structure of an NADP+-dependent enzyme to date (Matthews et al. (1977)). The crystallographic techniques used in the course of this work are discussed in Chapter 2. Particular attention is paid to the application of synchrotron radiation in protein crystallography in optimising heavy atom anomalous scattering. Appendix I also gives some experimental details relevant to this. Chapters 3, 4, and 5 give details of the structural results. In Chapter 3 the low resolution (6 Å) structure is presented with a full analysis of the derivatives (KAu(CN)2 and K2Pt(CN)4) used in the double derivative phase determination. The 6 Å electron density map could be interpreted. It showed the overall shape of the monomer and enabled the dimer axis to be identified. It also yielded the structurally interesting features of several long columns of density of the correct cross section for α-helix and also a cleft region. Chapter 4 is concerned with the determination of the coenzyme (NADP+) binding position at 6 Å resolution. Difference electron density maps calculated from X-ray measurements on crystals soaked in the oxidised coenzyme indicated the binding of NADP+ in the cleft region. Also, by using an iodinated derivative of the coenzyme, iodopyridine adenine dinucleotide phosphate (IADP+), it was possible to identify the nicotinamide moiety of the coenzyme and thus orient the coenzyme with respect to the enzyme. Chapter 5 describes the screenless rotation method and its application to the 2.6 Å crystallographic study of 6PGDH. In particular, the collection of the data for the native enzyme crystals and the K2Pt(CN)4 derivative. The phases calculated at 6 Å with two derivatives (as described in §3) were extended to 2.7 Å by calculating phases, using the photographic data, by the method of single isomorphous replacement with anomalous scattering. This enabled an electron density map to be calculated to 2.7 Å. Preliminary details of the quality of this electron density map are given.